Elevated temperature magnifies the toxicity of imidacloprid in the collembolan, Folsomia candida - You, Lelin; Gao, Ming; Damgaard, Christian; Zhu, Dong; Wang, Yifei; Xiao, Naichuan; Zhang, Tingting; Wang, Zifang; Dai, Wencai (Environmental pollution (1987), 2025)
Global warming subjects soil organisms to elevated temperature stress, while simultaneously altering the detoxification processes for pollutants within these organisms. The combined stressors of increased temperature and pollutants may impose synergistic stress on soil fauna, necessitating detailed investigation. Here, we exposed Collembola (Folsomia candida) to imidacloprid (a neonicotinoid pesticide) in combination with a range of constant temperatures in a full-factorial experimental design to assess the integrated impacts on survival, growth, and bioaccumulation. The results revealed that high temperatures and imidacloprid synergistically inhibited the survival of F. candida. Under 6.4 mg/kg imidacloprid exposure, survival rates decreased by 41.38 % at 30.2 °C and 68.75 % at 30.5 °C, compared to the same temperature treatments without imidacloprid exposure. Bayesian model analysis confirmed a significant synergistic interaction between imidacloprid and temperature on survival. Interestingly, at elevated temperatures, the internal concentration of imidacloprid in F. candida significantly decreased, while the soil concentration of the insecticide remained stable. This suggests that the observed synergistic effect is not due to increased pollutant accumulation within F. candida at higher temperatures, but rather the exhaustion of energy resources needed for detoxification and thermal stress management. This dual-stressor-induced energy competition underpins the synergistic interactions observed. Our findings highlight the significant synergistic effects of high temperatures and imidacloprid on Collembola, underscoring an increased ecological risk under such conditions. [Display omitted] •Elevated temperature and imidacloprid exposure jointly lower the survival rate of F. candida.•The internal imidacloprid concentration in F. candida declines as temperature rises.•Under combined stress, temperature notably affects body weight of F. candida.